2006
DOI: 10.1111/j.1365-2591.2006.01171.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of various automated devices on the shaping ability of Mtwo rotary nickel‐titanium instruments

Abstract: Both systems respected original root canal curvature well and were safe, indicating that the Mtwo direct handpiece is suitable for preparing curved root canals with the Mtwo instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
49
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 21 publications
10
49
1
2
Order By: Relevance
“…In the present study, straightening ranging from 6-10 degrees was registered. Other studies (11,19) reported straightening ranging from 1-2.69 degrees in teeth with an angle of canal curvature between 25 and 35 degrees. Our results suggest that the straightening tendency increases in conjunction with severe curvature.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the present study, straightening ranging from 6-10 degrees was registered. Other studies (11,19) reported straightening ranging from 1-2.69 degrees in teeth with an angle of canal curvature between 25 and 35 degrees. Our results suggest that the straightening tendency increases in conjunction with severe curvature.…”
Section: Discussionmentioning
confidence: 96%
“…In comparison with the crown-down procedure, Mtwo instruments allow more blades to be in contact with the canal at the same time, although this might result in a higher frictional resistance (19). Initial negotiation of root canal space is desirable by using hand files up to #15 in a watch-winding motion to assure the presence of a glide path (13) up to the foramen.…”
mentioning
confidence: 99%
“…Testing of fracture was carried out in a blinded manner to minimize bias. During canal instrumentation, only NaOCl was used for irrigation to avoid the potential impact of different irrigation solutions on dentin removal and fracture resistance as suggested in several previous studies (105)(106)(107)(108). The teeth were loaded without restoration of the endodontic cavities to avoid the confounding effects of enamel and dentin bonding restorative materials.…”
Section: Discussionmentioning
confidence: 99%
“…, Yang et al . ), and details regarding the design features of the Mtwo instruments have been published (Bürklein & Schäfer ).…”
Section: Introductionmentioning
confidence: 99%